2017
DOI: 10.1038/srep40067
|View full text |Cite
|
Sign up to set email alerts
|

The larvicide pyriproxyfen blamed during the Zika virus outbreak does not cause microcephaly in zebrafish embryos

Abstract: Although the zika virus (ZIKV) has now been strongly correlated with emerging cases of microcephaly in the Americas, suspicions have been raised regarding the use of pyriproxyfen, a larvicide that prevents mosquito development, in drinking water. The effects of this compound on neurodevelopment have not yet been addressed specifically in vertebrates. As a result, we aimed at addressing the effects, if any, of pyriproxyfen on neurodevelopment in the zebrafish embryo as a vertebrate model. Using zebrafish transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 42 publications
(51 reference statements)
0
21
0
2
Order By: Relevance
“…Our experiments show that cells treated with PPF alone do not readily form EVs (Figs. 2cii, iii and iv) and it is possible that PPF exposure by itself does not affect normal cellular functions [27]. However, an unusual behavior was observed when PPF-exposed cells were infected with VSV.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments show that cells treated with PPF alone do not readily form EVs (Figs. 2cii, iii and iv) and it is possible that PPF exposure by itself does not affect normal cellular functions [27]. However, an unusual behavior was observed when PPF-exposed cells were infected with VSV.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies, both using Zebrafish, have addressed the question of whether PPF could be implicated in microcephaly, each producing contradictory results (Dzieciolowska et al, 2017; Truong et al, 2016). One study (Truong et al, 2016) demonstrated that PPF induces adverse morphological changes including craniofacial defects in zebrafish at 5.2 μM (1.66 mg/L) - EC50.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, researchers have theorized that these birth defects could be because a new chemical, larvicide, was being used as a pesticide in Brazil's water supply beginning in 2015 to prevent the spread of mosquitoes. Research done on zebrafish has shown that this chemical is not the cause of microcephaly; although it is lethal in large doses, it does not cause any brain malformations (Dzieciolowska, 2017) This pesticide despite this conclusion on zebra fish may still be a possible reason on why the microcephaly problem is occurring most significantly in Brazil.…”
Section: The Brazilian Problemmentioning
confidence: 93%